Pengaruh Pemberian Insentif Covid-19 terhadap Kinerja Nakes Di RS X - Rositoh Rositoh; Gita Gloria Oktavia; Vanni Aldioni Putri (Syntax Corporation Indonesia, 2021)
In early January 2020, the world was shocked by a serious outbreak caused by a virus called Coronavirus Disease (COVID-19). The virus is believed to have first appeared on November 31, 2019 in wuhan city, China. The outbreak spread to several countries making it a global pandemic. The purpose of this study is to analyze the effect of covid-19 incentives on the performance of nakes in rs x. This research method as a whole uses quantitative methods. This study used two variables, namely bound variables and free variables, in this study it will be known if there is a significant influence between Incentive-Free Variables (X) to Performance Bound Variables (Y) in RS X. This study outlines the effect of Covid-19 incentives on Nakes' performance in Hospital X. This aims to find out how much impact Covid-19 incentives have on Nakes' performance in hospital X. Based on validation tests, reliability tests, simple linear regression tests, correlation coefficient tests, determination coefficient tests and t tests can be concluded that there is a significant influence between Covid-19 incentives on nakes performance in Hospital X by 34 .7% tested.